VMware vSphere design - Guthrie, Forbes, 1973- (Wylie Pub., 2011)
"The only book to cover how to properly design a VMware vSphere 4 implementation VMware vSphere is the industry's most widely deployed virtualization solution. The current release VMware vSphere 4 is considered the most robust and sophisticated virtualization product. This book is the only one of its kind to clearly and concisely show you how to create a vSphere 4 implementation so that it is tailored to meet a company's needs and resources. Expert authors share with you the factors that influence and shape the design of a vSphere 4 implementation. You will learn how to make the right design decisions for your company. Explores the newest release of VMware vSphere, the industry's most widely deployed virtualization solution Details the overall design process, server hardware, network layout, security, storage infrastructure, application ownership, and more Reviews everything you need to know in order to make the right decisions for using VMware vSphere 4 to meet your company's needs Shows you step by step how to use tools such as VMware vCenter Server Heartbeat, VMware vCenter Server Role Based Access Controls, CapacityIQ, vKernel, and more Packed with real-world examples, VMware vSphere 4 Design shows you just how the design for your company should ideally look--and how you can achieve that goal."--